Life Cycle Assessment of Silicon-Based Tandem Solar Photovoltaics and their End-of-Life - Marina Moneiro Lunardi; Juan Pablo Alvarez-Gaitan; Jose Bilbao; Richard Paul Corkish (Indonesian Journal of Life Cycle Assessment and Sustainability, 2018)
The rapid global uptake of solar photovoltaics (PV) promises the hope of affordable low-carbon electricity. Most production of PV modules so far, and for the foreseeable future, has been based on silicon wafer cells and while there are further R&D outcomes still to be fully transferred to the silicon cell industry, the next major technology change is likely to be the addition of a thin-film top cell to form an efficient tandem device. The authors have applied life cycle assessment (LCA) to several of the current and potential mass manufactured solar cell technology choices, including different silicon wafer styles and silicon/thin-film tandems. We have demonstrated that the environmental benefits of some paths for efficiency improvements, particularly of the incorporation of atomic hydrogen into silicon wafers, more than compensate for the additional inputs required. Furthermore, we have shown that the stability of top-cell materials for tandems is paramount, to avoid the premature demise of the underlying silicon bottom cell.The end-of-life has been assumed to be landfill in most preceding LCA studies but there is a growing global need for PV recycling due to the rapid rise in uptake of photovoltaics, which will result in a significant future waste stream. Europe is leading the world in requiring industry stewardship for photovoltaics (and batteries, inverters and other system components) and other jurisdictions, including Australia, are following. However, photovoltaic modules are difficult to dismantle or deconstruct for materials recovery by methods that are both financially and environmentally sustainable. We will use LCA to guide our research on module recycling by chemical, thermal and mechanical methods and their combinations, with an aim to maximize the value of the recovered materials.